Influence of Airflow Leakage on Rotary Regenerator Performance Factors (University of Khartoum Engineering Journal, 2022)
This work investigated the influence of airflow leakage on the regenerator performance factors of effectiveness (ε), airflow capacity (C*), matrix capacity (Cr*) and number of transfer unit (NTU). A sophisticated experimental setup that facilitates precise measurement of apparent airflow temperature, rate and pressure drop is used. The measurements covered a wide range of rotational speeds (0 - 24 rpm), regeneration temperatures (40 – 70 °C) and airflow rates (160-500 kg/h). The range of apparent performance factors is for C* (0.95-1.00), Cr* (0.21-62.53), NTU (3.5-12.76) and ε (0.17-0.78). Significant difference between the real and apparent performance factors was found even under small leakage percent. The deviation of the real from the apparent effectiveness expressed as absolute average percent deviation (AAPD) exceeded 6. In over 300 data points AAPD for C*, Cr* and NTU exceeded 12, 7 and 7, respectively. The work also provided a relationship that facilitates the determination of the real airflow temperature and the rate from the apparent (i.e. measured) values.